DETERMINATION STRENGTH OF LATERITE STABILISED WITH CEMENT AS A BINDER AGENT - Ismail, G.; Jais, I. B. M. (Journal of Engineering and Technology (JET), 2025)
This paper investigates the effect of a chemical stabiliser, which is cement, on the strength of laterite soil to act as a subgrade for the pavement layer. The analysis will focus on the improvement of laterite soil's strength withstanding the load applied during the Unconfined Compressive Strength (UCS) test. Cement was utilised as the stabiliser in this method. According to the UCS, cement content rises in strength. Sub-grade or Soil stabilisation is a technique to increase the pavement layer's strength by altering the soil's chemical and mineral composition using chemical additives or non-chemical additives as the stabilising agents.